Causes of Enrollment Disparities of Students with Disabilities in Tanzania Secondary Schools - Kambuga Yusuph; Hussein Hussein (Indonesian Journal of Disability Studies, 2022)
This article argues that children with disabilities face significant obstacles in schooling in Tanzania, despite the government initiative to formulate policy and awareness creation for people with disabilities. This paper examined the causes of enrollments disparities of students with disabilities in the schooling system in Tanzania. Three objectives were addressed regarding enrollment trends from 2016 to 2020, causes leading to disparities in enrolments, and obstacles facing students with disabilities in non-inclusive schools. Documentary analysis and interview methods were used to collect information. The participants were special needs educators and students from secondary schools and universities. The findings reveal disparities in enrollment of students with disabilities as they advance from lower to higher levels of schooling. The analysis shows that the smaller number of students with disabilities in the schooling system was attributed to a lack of awareness among parents on the educational services provided to children with disabilities, traditional beliefs, poverty, stigma, and harassment. The analysis further shows that shortage of qualified teachers, poor school infrastructures, and unsupported inclusive classrooms was among many obstacles facing students with disabilities in schools.